Towards A Biblical Model of Counseling - Carter, John D. (Journal of psychology and theology, 1980)
This article attempts to develop a model of counseling which is biblical in structure and which is contrasted to two inadequate alternatives. The model is developed for the Scriptures' description of the Flesh and the Spirit and centers on therapeutic relationship as expressed in six dimensions: goal setting, source of value, locus of responsibility, focus on cognition/feeling/behavior, style of therapy, and duration of therapy.